In ovulo rescue of hybrid embryos in flame seedless grapes - influence of pre-bloom sprays of benzyladenine - Bharathy, P. V.; Karibasappa, G. S.; Patil, S. G.; Agrawal, Dinesh C. (Scientia Horticulturae, 2005)
Based on the theory that cytokinins are known to increase the sink strength of seeds for assimilates, the present investigation was carried out to study the influence of pre-bloom and bloom time sprays of benzyladenine (BA) on embryo recovery, germination and plant development in Flame Seedless grape variety by using in ovulo rescue methods. The combined effect of pollen parent type and sprays of BA drastically improved these parameters and the embryo recovery was more than doubled in all the crosses, except in cross FS x Concord. Also, germination of embryos was higher when BA sprays were given. Recovery of embryos and growth depended on BA treatment and the pollen parent types. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: benzyladenine; flame seedless; in ovulo embryo rescue; interspecific hybridization; Vitis spp.

High frequency occurrence of single cotyledonary embryo morphotype and repetitive somatic embryogenesis in `Thompson Seedless' crossed with seven grapevine male parents - Bharathy, P. V.; Agrawal, Dinesh C. (Vitis, 2008)
Direct somatic embryogenesis was observed in zygotic embryos rescued from intra- and inter-specific crosses between `Thompson Seedless' and seven male parents of grapevine when the embryos were cultured on Woody Plant Medium (WPM) supplemented with benzyladenine (1 mu M). Repetitive somatic embryogenesis occurred on the same medium, which also supported a high percentage of embryo maturation, germination and plantlet development. The cultures retained embryogenic potential for more than two years. We observed a high frequency occurrence of mono-cotyledonous embryo morphotype and other morphological variations in somatic embryos of all the crosses. The percentage of embryos having mono-, di-, tri-, multiple and abnormal cotyledons varied among the crosses. The overall percentage of monocot embryos was 35.50 %, as against 38.64 % of dicot embryos, while the germination rates for mono- and dicot- embryos were 24.44 % and 24.15 %, respectively. Shoot development was poor in tri- and multiple-cotyledonary embryos, while there was no shoot formation in abnormal embryos. We assume that the relatively high occurrence of single cotyledonary morphotype, may be due to the repetitive exposure of embryogenic tissues to a medium containing benzyladenine.
Keywords: cotyledon; Grapevine; somatic embryo; Vitis